Molecular epidemiology of non‐syndromic autosomal recessive congenital ichthyosis in a Middle‐Eastern population. Issue 9 (15th April 2021) - Mohamad, Janan; Samuelov, Liat; Malchin, Natalia; Rabinowitz, Tom; Assaf, Sari; Malki, Liron; Malovitski, Kiril; Israeli, Shirli; Grafi‐Cohen, Meital; Bitterman‐Deutsch, Ora; Molho‐Pessach, Vered; Cohen‐Barak, Eran; et al.
Abstract: Autosomal recessive congenital ichthyosis (ARCI) is a rare and heterogeneous skin cornification disorder presenting with generalized scaling and varying degrees of erythema. Clinical manifestations range from lamellar ichthyosis (LI), congenital ichthyosiform erythroderma (CIE) through the most severe form of ARCI, Harlequin ichthyosis (HI). We used homozygosity mapping, whole‐exome and direct sequencing to delineate the relative distribution of pathogenic variants as well as identify genotype‐phenotype correlations in a cohort of 62 Middle Eastern families with ARCI of various ethnic backgrounds. Pathogenic variants were identified in most ARCI‐associated genes including TGM1 (21%), CYP4F22 (18%), ALOX12B (14%), ABCA12 (10%), ALOXE3 (6%), NIPAL4 (5%), PNPLA1 (3%), LIPN (2%) and SDR9C7 (2%). In 19% of cases, no mutation was identified. Our cohort revealed a higher prevalence of CYP4F22 and ABCA12 pathogenic variants and a lower prevalence of TGM1 and NIPAL4 variants, as compared to data obtained in other regions of the world. Most variants (89%) in ALOX12B were associated with CIE and were the most common cause of ARCI among patients of Muslim origin (26%). Palmoplantar keratoderma associated with fissures was exclusively a result of pathogenic variants in TGM1 . To our knowledge, this is the largest cohort study of ARCI in the Middle‐Eastern population reported to date. Our data demonstrate the importance of population‐tailored mutation screening strategies and shed light upon specific genotype‐phenotype correlations.